Mucormycosis in Children With Hematologic Malignancies: A Case Series and Review of the Literature. Issue 9 (13th June 2022) - Loeffen, Yvette G. T.; Scharloo, Fenna; Goemans, Bianca F.; Heitink-Polle, Katja M. J.; Lindemans, Caroline A.; van der Bruggen, Tjomme; Hagen, Ferry; Wolfs, Tom F. W.
Abstract : Background: Mucormycosis is classified as the third leading cause of invasive fungal disease in immunocompromised patients and is characterized by high morbidity and mortality (33%–56%). The aim of this study is to describe presentation, treatment and outcome of Dutch pediatric hemato-oncology patients recently diagnosed with mucormycosis and to review the literature to gain more insight specifically into contemporary outcome data. Methods: Ten cases were diagnosed in the Princess Máxima Center for Pediatric Oncology from 2018 to 2021 and were retrospectively reviewed. In addition, 9 case series (n = 148) were included from literature. Results: In our case series, 5 patients of 10 children (age 2–17 years) had disseminated invasive fungal disease. Four patients had localized pulmonary disease and 1 had a localized renal infection. One diagnosis was made postmortem. The underlying diseases were acute lymphoblastic leukemia (n = 6), acute myeloid leukemia (n = 2) and lymphoma (n=2). Seven patients received combination therapy comprising of a lipid amphotericin B formulation and a triazole, surgery was performed in 67%. All neutropenic patients received granulocyte transfusions and/or granulocyte colony-stimulating factor. Mucormycosis-related mortality was 20%. In the literature review, mucormycosis-related mortality was 36% for all patients and 66% for patients with disseminated disease. Survival rates were similar over the past 2 decades. The most common underlying disorder was acute lymphoblastic leukemia. Liposomal amphotericin B was the mainstay of treatment. Seventy percent of patients underwent surgery. Conclusions: Although survival of mucormycosis improved significantly overtime, it plateaued in the past decades. This series shows that with screening, early diagnostics and early antifungal and if possible surgical treatment, mortality is low and even disseminated disease is salvageable if approached aggressively with a combination of surgery and antifungal treatment. Further research focused on diagnostics, combination antifungal and adjunctive therapy is necessary to enhance the survival of mucormycosis in children.